Structural and Hirshfeld surface analysis of thallium(I) and indium(III) complexes of a soft scorpionate ligand - Fujisawa, Kiyoshi; Kuboniwa, Ayaka; Tan, Sang Loon *; Tiekink, Edward R. T. * (MDPI, 2023)
Two complexes containing a soft sulfur-substituted tris(pyrazolyl)hydroborate ligand, namely [TlI(TmtBu)]2∙2H2O and [InIII(TmtBu)2](InCl4), where TmtBu is the tris(3-tert-butyl-2-sulfanylidene-1H-imidazol-1-yl)hydroborate anion, have been characterized. The {TlS}2 core of the former has the shape of a diamond. Each S atom of the TmtBu anion coordinates differently: one S is connected to one Tl atom, one bridges both Tl atoms, while the third S atom connects solely to the second Tl atom. The S4 donor set defines a seesaw geometry. The independent H2O molecule forms O–H···S and localized O–H···π(pyrazolyl) contacts. Flattened octahedral geometries defined by S6 donor sets are noted for the two independent cations in [InIII(TmtBu)2](InCl4). In the crystal of [TlI(TmtBu)]2∙2H2O, pyrazolyl-C–H···O(water) interactions connect the dimeric units into a linear supramolecular chain, chains pack without directional interactions between them. In the crystal of [InIII(TmtBu)2](InCl4), alternating rows of independent cations are interspersed by anions. The primary points of contact within a three-dimensional architecture are of the type In–Cl···π(pyrazolyl) and C–H···Cl. The assessment of the molecular packing was complemented by considering the calculated Hirshfeld surfaces and two-dimensional fingerprint plots (overall and delineated into individual contacts).